THE FEMININE STYLE OF MANAGEMENT AND SUCCESS IN ORGANIZATIONS AS EXEMPLIFIED BY TECHNOLOGY STARTUPSPS - Makowiec, Marek (Management and Administration Journal, 2021)
The article contains considerations on the identification and verification of the impact of gender, and especially the feminine style of management on the success of an organization, with particular emphasis placed on technology startups. It presents examples confirming that women are better equipped to cope with problems in running this type of organization, as compared to men in the same positions. In the course of analysis, it was possible to identify the distinguishing features and characteristics of the female (modern) style of management in the context of startups.